2005
DOI: 10.1016/j.jviromet.2005.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Yeast expression and characterization of SARS-CoV N protein

Abstract: The severe acute respiratory syndrome human coronavirus (SARS-CoV) nucleocapsid protein (N protein) is its most antigenic structural protein. The N protein gene has been cloned into a yeast expression vector pPIC9, transformed into Pichia pastoris strain GS115 and induced for expression by methanol. SDS-PAGE and Western blot showed that the N protein was expressed at a level of 3mg/ml of culture medium. Characterization by mass spectrometry, circular dichroism and fluorescence luminescence assays showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…We observed that during extraction of inclusion bodies, IMAC purification and upon storage at 4 • C, NP exhibited some degradation which was also reported previously (Tang et al, 2005). This is due to the low stability of NP of SARS-CoV since it is the only SARS-CoV protein which contains no Cys residues (Cao et al, 2005). It is also reported that SARS virus looses its infectious capacity at 56 • C and the low stability of the NP may be at least one of the important determinants for the thermosensitivity of SARS virus (Duan et al, 2003).…”
supporting
confidence: 83%
“…We observed that during extraction of inclusion bodies, IMAC purification and upon storage at 4 • C, NP exhibited some degradation which was also reported previously (Tang et al, 2005). This is due to the low stability of NP of SARS-CoV since it is the only SARS-CoV protein which contains no Cys residues (Cao et al, 2005). It is also reported that SARS virus looses its infectious capacity at 56 • C and the low stability of the NP may be at least one of the important determinants for the thermosensitivity of SARS virus (Duan et al, 2003).…”
supporting
confidence: 83%
“…In this study, we explore the possibility of using yeast expression system as an efficient and low-cost option to supplement the bacterial system. Previous reports have demonstrated the feasibility of using the P. pastoris as host to express the SARS-CoV proteins, including the membrane [9] and the nucleocapsid [10,11] protein. Although Lu et al [12] expressed a small fragment of the S1 domain (amino acid residues 251-561) in the P. pastoris, they had not demonstrated the ability of this fragment to specifically pulldown ACE2 from cell lysate.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies of SARS-CoV, MERS-CoV, and SARS-CoV-2 SARS-CoV is a coronavirus with a diameter of approximately 100 nm. Coronaviruses are the largest +ssRNA viruses and contain at least 14 ORFs, 16,55 among which five main ORFs encode the replicase (Rep), and the S, E, M, and N proteins. 56 protein combines with viral RNA to form a nucleocapsid, which is involved in the replication of SARS-CoV and is the most abundant protein in virus-infected cells.…”
Section: Epidemiological Analysis and Symptoms Of Sars Mers And Cormentioning
confidence: 99%